An Analysis of the Arabic Language Textbook for Seventh Grade Students at Madrasah Tsanawiyah - Shobrun Jamil; Ade Ruswatie; Muhammad Aqsho; Maskanatul Fiqiyah (Universitas Islam Negeri Raden Intan Lampung, 2025)
Many textbooks, including those for Arabic language, exhibit weaknesses in terms of language or content. Research on textbooks is extensive, especially with diverse contents. Errors in Arabic language textbooks can be attributed to linguistic issues, including errors, mistakes, and lapses. In the realm of Arabic linguistic analysis, errors can arise in areas such as syntax (nahwu), morphology (sharaf), and others, even in textbooks developed by reputable institutions that ideally should be error-free. This study aimed to calculated, explained, and analyzed the sharps of error in Arabic textbook which arose in the most crucial aspects of Arabic language. This type of research was content analysis research, which aimed to analyze more deeply the content of Arabic textbooks for the class VII in Madrasah Tsanawiyah. The method used was the study of documentation. This research was expected to contribute to improving the quality of Arabic textbooks and Arabic language education in Indonesia. The results of this research can also be used as a reference to improve the quality of writing Arabic textbooks in the future. Conducting a feasibility analysis of Arabic language textbooks is considered essential to ensure that they meet the necessary criteria for effective learning.